Teksty Polaków pisane grażdanką w syberyjskiej wsi Wierszyna - Natalia [Наталия, Nataliia] Ananiewa [Ананьева, Anan’eva] (Acta Baltico-Slavica, 2015)
Polish texts in Cyrillic alphabet used by the speakers of the Polish dialect in the village of Vershina